The Provision of Financial Management Training for Micro, Small, and Medium Enterprises (MSMEs) in Roti Putra Solo - Olga, Lidia; Rahman, Taufik; Djago Djoa, Dominikus; Arifin, Zaenal (LPPM Sekolah Tinggi Teknologi Nusantara Lampung, 2023)
The growth of Micro, Small and Medium Enterprises (MSMEs) can only be seen in their quantity, while quality and development are still unsatisfactory. In general, one of the weaknesses, especially in the financial aspect, is that only a few MSMEs have experienced development in their financial performance. This is due to the lack of awareness of MSMEs actors regarding the importance of financial management in the company.Financial management is one of the essential aspects of the company’s progress, especially MSMEs. This is because the actors are faced with human resource problems. Financial management can be done through accounting, even though the standards are basic and straightforward. Accounting is a systematic process to generate financial information that can be used for decision-making by users.As long as MSMEs still use money as their transaction tool, accounting is greatly needed by MSMEs. The existence of financial/accounting reports will provide several benefits for MSMEs actors.